Uji Aktivitas Antioksidan Esktrak Kasar dan Terpurifikasi Daun Salam (Syzygium polyanthum) - Dwi Wahyuni; Rosa Juwita Hesturini; Krisna Pertiwi (JUSTER : Jurnal Sains dan Terapan, 2025)
Bay leaves (Syzygium polyanthum) are one of Indonesia’s biological resources that have long been utilized, particularly as a cooking spice and in traditional therapy. Current use by the public is still largely based on empirical evidence, and scientific validation is still needed to support its application. The aim of this study was to determine the antioxidant capacity of both crude and purified bay leaf extracts. Extraction was carried out using the maceration method with 96% ethanol as the solvent. Purification of the extract was performed using a liquid-liquid extraction method with a solvent ratio of ethanol to n-hexane = 1:1. Phytochemical screening was conducted on both the crude and purified extracts. Antioxidant activity was evaluated using the DPPH method. Free radical scavenging was measured by UV-Vis spectrophotometry at the maximum wavelength. The results of phytochemical screening indicated that both crude and purified extracts contained alkaloids, flavonoids, tannins, and saponins. The maximum absorbance wavelength was found at λ = 514 nm. The antioxidant activity (IC₅₀) of the crude and purified bay leaf extracts was 15.120 ± 0.039 ppm and 13.293 ± 0.039 ppm, respectively. These results indicate that bay leaves possess strong antioxidant potential.